CHILDHOOD CHRONIC ILLNESS: HOW DOES IT AFFECT THE FUTURE CAREER GOALS OF THE INDIVIDUAL? - Staniec, Elisa (East Carolina University, 2021)
The purpose of this study is to investigate the negative impacts of chronic illness on future development and career choices in young adulthood. Young adults with a chronic illness diagnosed in childhood are challenged with illness-related stressors in addition to developmental stressors as they age. There is a need to better understand the direct impacts and potential for mediating factors that contribute to career choice in this population. The aims of this study are to emphasize the possibility of success to the future generations of children diagnosed with a chronic illness, with skills learned from childhood experiences, by pursuing healthcare careers. Secondary data was analyzed using the National Survey of Youth 1997 cohort. Overall results using regression suggest chronic illness had a significant impact on depression, limitations, and independence in adulthood. However, there is no significant relationship between childhood chronic illness and healthcare professions as a career path. Depression was found to mediate the association between childhood chronic illness and pursuing healthcare professions.
Keywords: career outcomes; life-course theory; feminist theory; psychosocial developmental theory; child life specialists; Chronic diseases in children--Social aspects; Medicine--Vocational guidance; Career development